Foucault on the Wards: Rediscovering Reflection as a Social Pediatrician in Training. (15th October 2019) - Maynard, Kevin
Abstract : The author states that as a second-year medical student with a liberal arts degree, it is often difficult for him to reconcile his former education with the current demands of his training. Although the medical curriculum acknowledges the importance of a biopsychosocial model, the prioritization of knowledge remains the same: know your biological, pharmacological, and anatomical facts. However, the author's experience with a social pediatrics research summer studentship moved him beyond this basic sciences mindset and provided a practical framework for the application of his liberal arts training. The experience was twofold: he worked on a research project while simultaneously shadowing a pediatrician twice a week. His project applied a Foucauldian critical discourse analysis to an archive of texts that sought to better characterize the term social pediatrics. The author concludes that the thought-changing reflection, mentorship, and concrete clinical experiences made possible by the summer studentship expanded his worldview.